New potent imidazoisoquinolinone derivatives as anti-Trypanosoma cruzi agents: biological evaluation and structure-activity relationships - Bollini, Mariela (2009)
A series of novel benzoimidazo and N-aryl-5-oxo-imidazo[1,2-b]isoquinoline-10-carbothioamides was developed. All the compounds were evaluated for their in vitro action against the epimastigote form of Trypanosoma cruzi. Four of them showed higher activity than Nifurtimox. Their unspecific cytotoxicity was evaluated using HeLa and L6 cells, being non-toxic at concentrations at least 15 and 200 times higher than that of T. cruzi IC(50.) To gain insight into the mechanism of action, their DNA binding properties and reactivity with glutathione were studied, and QSAR study was performed.